AI-Based Dynamic Pricing in Online Transportation Services: A Legal Review of Algorithmic Fairness and Transparency - Abed Nego Marpaung; Thea Farina; Nuraliah Ali (Eduvest - Journal of Universal Studies, 2026)
The development of Artificial Intelligence (AI) has significantly transformed the digital economy, including app-based transportation services. One of the most debated applications of AI is dynamic pricing, a mechanism that automatically adjusts fares based on real-time market demand and supply fluctuations. In Indonesia, this practice raises legal issues related to consumer protection and economic fairness, particularly when prices surge drastically during emergencies. The lack of algorithmic transparency in fare determination raises concerns about fairness for consumers and the balance of interests among service providers, drivers, and users. This study aims to analyze the legal implications of dynamic pricing under Indonesia’s Consumer Protection Law and Trade Law, and to formulate regulatory recommendations ensuring that AI-based pricing systems remain ethical and fair for all parties. The research employs a normative legal method using three main approaches: a statutory approach to examine relevant legal frameworks, a conceptual approach to explore theories of price fairness and digital consumer protection, and a comparative approach to assess dynamic pricing practices in other countries. Data are collected from primary and secondary legal sources, as well as in-depth interviews with key stakeholders, including government regulators, transportation service providers, drivers, consumers, and digital law experts. The findings are expected to provide concrete recommendations for regulating AI-driven dynamic pricing in online transportation services, thereby promoting a balance between consumer protection, algorithmic transparency, and the sustainability of Indonesia’s digital economy.